2016
DOI: 10.7863/ultra.15.11068
|View full text |Cite
|
Sign up to set email alerts
|

Basic Abdominal Point‐of‐Care Ultrasound Training in the Undergraduate

Abstract: Teaching based on peer mentoring achieved an adequate level of training in basic abdominal ultrasound. The students acquired these skills in a relatively short training period. These results suggest that peer mentoring can facilitate the large-scale implementation of ultrasound teaching in undergraduate students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 31 publications
0
29
0
1
Order By: Relevance
“…A non-physician astronaut aboard the International Space Station successfully completed a FAST exam in 5.5 minutes with only brief training and voice assistance by a ground-based ultrasound expert. [5] A study from Spain by Garcia-Casasola et al [14] reported that 4 th year medical students with over 15 hours of hands-on training correctly imaged and identified the liver, spleen, and kidneys over 95% of the time, while the heart via the subxiphoid view had the lowest rate at 55%. In another study, after a three-day college POCUS course in the United States, premedical college students self-rated performing bladder ultrasound as their strongest area (4.86 on Likert scale), while obtaining the subxiphoid view their weakest area (4.40).…”
Section: Discussionmentioning
confidence: 99%
“…A non-physician astronaut aboard the International Space Station successfully completed a FAST exam in 5.5 minutes with only brief training and voice assistance by a ground-based ultrasound expert. [5] A study from Spain by Garcia-Casasola et al [14] reported that 4 th year medical students with over 15 hours of hands-on training correctly imaged and identified the liver, spleen, and kidneys over 95% of the time, while the heart via the subxiphoid view had the lowest rate at 55%. In another study, after a three-day college POCUS course in the United States, premedical college students self-rated performing bladder ultrasound as their strongest area (4.86 on Likert scale), while obtaining the subxiphoid view their weakest area (4.40).…”
Section: Discussionmentioning
confidence: 99%
“…[45] We therefore chose to focus on splenic microabscesses, as they are relatively easy for a clinician with limited ultrasound experience to identify. [46,47] Given that POCUS is cheap and portable, and provides data rapidly to the treating clinician, ultrasound evaluation of the spleen in patients with HIV and symptoms suggestive of TB is a beneficial addition to diagnostic and treatment algorithms in resource-limited settings.…”
Section: Discussionmentioning
confidence: 99%
“…Se han realizado estudios en estudiantes en quienes se consigue alcanzar un alta sensibilidad diagnostica tras un entrenamiento en ecografía [13,14]. En la mayor parte de los programas de residencia de reumatología en España, se contempla la enseñanza de la ecografía a pie de cama como una herramienta de ayuda diagnóstica y para las punciones y aspiraciones de liquido sinovial.…”
Section: Editorialunclassified